2004
DOI: 10.1128/jvi.78.7.3572-3577.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prior Infection and Passive Transfer of Neutralizing Antibody Prevent Replication of Severe Acute Respiratory Syndrome Coronavirus in the Respiratory Tract of Mice

Abstract: Following intranasal administration, the severe acute respiratory syndrome (SARS) coronavirus replicated to high titers in the respiratory tracts of BALB/c mice. Peak replication was seen in the absence of disease on day 1 or 2, depending on the dose administered, and the virus was cleared within a week. Viral antigen and nucleic acid were detected in bronchiolar epithelial cells during peak viral replication. Mice developed a neutralizing antibody response and were protected from reinfection 28 days following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
495
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 410 publications
(524 citation statements)
references
References 30 publications
27
495
0
2
Order By: Relevance
“…Four weeks after the second immunization, animals were challenged i.n. with 10 4 tissue culture 50% infective dose (TCID 50 ) of SARS-CoV as described (14). Two days later, the lungs and nasal turbinates of four animals in each group were removed and the SARS-CoV titers were determined (14).…”
Section: Elisamentioning
confidence: 99%
See 2 more Smart Citations
“…Four weeks after the second immunization, animals were challenged i.n. with 10 4 tissue culture 50% infective dose (TCID 50 ) of SARS-CoV as described (14). Two days later, the lungs and nasal turbinates of four animals in each group were removed and the SARS-CoV titers were determined (14).…”
Section: Elisamentioning
confidence: 99%
“…Neutralizing antibody was determined by the inhibition of cytopathic effects mediated by SARS-CoV on Vero cell monolayers as described (14). The dilution of serum that completely prevented cytopathic effect in 50% of the wells was calculated (27).…”
Section: Elisamentioning
confidence: 99%
See 1 more Smart Citation
“…Animals depleted of both CD4 and CD8 T cells generally do not control the infection, despite substantial production of anti-IAV IgM antibodies (4,23,33,34). However, adoptive transfer of IAV-specific IgM or IgG antibodies is protective (40,51), suggesting that the timing and magnitude of the antibody response, i.e., the affinity, avidity, and antibody isotype, are important protective factors.…”
mentioning
confidence: 99%
“…All these reports point to that it will be important to establishan appropriatecombination of vaccination route, vaccine vector andchoice of epitopes for each vaccine type.SARS vaccines thatgeneratea predominantly cellular or a predominantly humoral response, as well as therapeutic monoclonal antibodies, have been shown protectiveeffects in animal models. Therefore, what kind of responses are important for protection has not been clear (Subbarao et al, 2004;Zakhartchouk et al, 2005;Lin et al, 2007;See et al, 2008;Zhao and Perlman, 2010). Cameron et al (2012) have recently reported an analysis of transcripts expressed during SARS-CoV infection in vaccination and reinfectiontrials in ferrets (Cameron et al, 2012).…”
Section: Vaccines and Immunotherapy For Sars-covmentioning
confidence: 99%